Nonlinear Impulsive Integrodifferential Equations with Nonlocal Conditions in Banach Spaces - et al., Venkatesan (International Journal of Advanced Science and Technology, 2019)
We study the existence and uniqueness of mild and classical solutions for a impulsive integro-differential systems with nonlocal conditions By combining and extending some earlier work on equations with nonlocal condition and equations with impulsive condition. Here, is the generator of a strongly continuous semigroup in a Banach space (BS), Here . is a continuous nonlocal condition, and constitutes in impulsive condition. New results are obtained.